The development of a tool for investigating the barriers and supports to participation in school life and feelings of belonging: part 1 - McDermott, T; Porter, J; Ingram, J; Daniels, H (Routledge, 2020)
Students’ experience of learning, relating and belonging are crucial to their participation in school. With ever growing concern about young people’s mental health and levels of informal and formal exclusion it is timely to investigate how schools can be supported in meeting the social and psychological needs of learners. The focus of this paper is the development of a questionnaire to investigate the relationship between pupils’ experience of belonging and the barriers they encounter in the school setting. Our aim was to test out the tool prior to full standardisation. Data was collected from 722 students across four secondary schools. Four factors were identified within the scale with one factor, that which measured emotional security and comfort, demonstrating moderate correlations to all other scales indicating that it had an underlying relationships to different aspects of the school environment. Students who disclosed SEND had a greater likelihood of demonstrating low connectedness than would be expected by chance alone, with some differences in the degree to which particular items were predictive of overall levels of connectedness.